Improved gfp and inaZ Broad-Host-Range Promoter-Probe Vectors - William G. Miller; Johan H. J. Leveau; Steven E. Lindow (Molecular Plant-Microbe Interactions, 2000)
A new set of broad-host-range promoter-probe vectors has been constructed. One subset contains the pVS1 and p15a replicons and confers resistance to either gentamicin or kanamycin. The other set contains the broad-host-range replicon from pBBR1 and confers resistance to kanamycin, tetracycline, ampicillin, or spectinomycin/streptomycin. Both plasmid sets are highly stable and are maintained without selection for more than 30 generations in several bacterial taxa. Each plasmid contains a promoter-probe cassette that consists of a multicloning site, containing several unique restriction sites, and gfp or inaZ as a reporter gene. The cassette is bound by transcriptional terminators to permit the insertion of strong promoters and to insulate the cassette from external transcription enabling the detection of weak or moderate promoters. The vector suite was augmented with derivatives of the kanamycin-resistant gfp promoter-probe plasmids that encode Gfp variants with different half-life times.